Kajian Perkembangan Lahan Permukiman Berdasarkan Kemampuan Lahan Pada Kawasan Rawan Banjir di Perkotaan Pemalang - Aldian, Shafa Kautsara; Pigawati, Bitta (Teknik PWK (Perencanaan Wilayah Kota), 2024)
Settlement development is related to population growth. High population growth causes an increase in demand for residential land. During a period of 5 years (2016 - 2020) there was an increase in the number of residents and  the number of residential buildings. Currently, there are several settlements in the Pemalang Urban Area which are in flood-prone areas. This study aims to analyze the suitability of residential land development in flood-prone urban areas of Pemalang based on land capability. Using a quantitative descriptive method with a spatial approach. The results of the research show that the development of settlements occurs in locations that are in accordance with the capabilities of the land. The development of this settlement was found to occur in a flood-prone area. There is a moderate flood-prone potential of 5.36 Ha (2.47%) and a high flood-prone potential of 211.32 Ha (97.53%). Location of settlement development that is not in accordance with the Regency Spatial Planning Document Pemalang covers an area of 10.01 ha, distributed in 13 sub-districts.